Definição e seleção de projetos de suporte à governança participativa na gestão de recursos hídricos utilizando a árvore da realidade atual como ferramenta na identificação de conflitos - Ferreira, Luciana Kamila Rodrigues (2023)
Water Resources Management aims to meet society’s need for water, considering limitations in its availability, economic and environmental restrictions, and also the principles of social justice. Brazilian Law nº 9.433/97, which establishes the National Water Resources Policy (PNRH), emphasizes the participation of different stakeholders, including public authorities, water users, and the community, in a decentralized and participatory management, since water is a public good. For this participatory management model to be effective, it is crucial that civil society and water users understand their role in the use and appropriation of water resources. However, one of the main challenges is the lack of technical knowledge and access to the necessary information to support the decision-making process. These barriers limit the participation of society in general, making the deliberation depend mainly on the perspectives of the technical-scientific staff and the Committee managers. This issue is compounded in regions of Brazil where water scarcity is a notable feature, as is the case of river basins in the State of Ceará, where the scarcity of rainfall is caused by climate irregularity and environmental degradation. Thus, this work aims to define and select projects which support participatory governance inWater Resources Management, using as inputs the problems within the scope of the Acaraú River Basin Committee. For this, an extensive review on bibliography regarding Participatory Governance andWater ResourcesManagement (WRM) was carried out to search available studies on these matters, which showed a literature gap and justified this research. A case study was carried out to identify and analyze the relationship between causes and effects of problems (conflicts) and root causes in the Acaraú River Basin Committee located in the state of Ceará, Brazil, by examining the minutes of Committee meetings occurred between 2005 and 2021. In order to mitigate the problems, improvement projects were proposed. As main results, 102 problems were identified (chained by cause-and-effect relationships), in addition to 18 improvement projects that were proposed, whose intention is to stimulate and promote the effective participation and involvement of the civil community in the decisionmaking process in the context of participatory management, essential toWRM.